An investigation of mathematics preservice teachers' noticing skills - Tün, Sena Simay. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
As student centered teaching approaches have become popular in recent years, teachers’ noticing skills in terms of attending to students’ mathematical thinking, in terpreting their thinking and responding to them have become one of the prominent issues investigated by scholars. Studies revealed that preservice teachers’ noticing skills can be improved through analysis of videos of their own teaching. In this study, the progress in preservice teachers’ noticing skills through and after an intervention was investigated. Throughout the 2016-2017 academic year, two preservice mathematics teachers worked with 7th grade students on the mathematical tasks about numbers, algebra, data analysis and geometry. Data were collected through videos of preservice teachers’ interactions with students during task implementations, videos of their oral reﬂections just after implementations and their written reﬂections about implementa tions. The researcher identiﬁed mathematical opportunities (MOST) occurred during the implementations and these MOST instances were used as a medium to investigate in the noticing skills of preservice teachers. The attending, interpreting and respond ing level of preservice teachers during the implementation of mathematical tasks were analyzed according to coding scheme. The analysis of data revealed that preservice teachers attended to majority of the mathematical opportunities (approximately %84) occurred during task implementations. In addition to this, they interpreted possible reasoning behind students’ thinking in their written reports. However, their respond ing for such opportunities were mostly in the form of orienting students for correct answers rather than eliciting their conceptual understanding. Therefore, video analy sis and written reports might be eﬀective tools to improve preservice teachers’ noticing skills.
Keywords: Mathematics teachers.; Student teaching.